Mencintai Alam: Perspektif Agustinus Dari Hippo - Grace Son Nassa (Sekolah Tinggi Teologi Arastamar Bengkulu, 2022)
This research is motivated by an ecological crisis that cannot be separated from the spiritual crisis of mankind. This research is constructive and offers a way of loving nature based on the perspective of Augustine from Hippo. The method used is content analysis, which requires the author to analyze primary and secondary writings related to the topic and then draw important points, process and present them in the form of descriptions. This research shows that Augustine's perspective on loving nature is significant for the current ecological crisis because Augustine does not agree with the utilitarian point of view in looking at nature and even suggests throwing it away because it is very detrimental to nature. In addition, renewal of the senses, mind, and heart, and contemplating God in nature and nature in God becomes a necessary thing and a way that can be used in an effort to love nature. These three things can be a positive contribution to efforts to find ways to love nature which are currently critical.